Society and democracy in Europe - Gabriel, Oscar W., 1947-; Keil, Silke I., 1967- (London : Routledge, 2013)
'This comparative book examines what kinds of societal forces shape an individuals' relationship towards democratic political life in contemporary Europe'--
Includes bibliographical references and index.
Keywords: Political participation -- Europe; Democracy -- Europe